Studi Perbandingan Antara Hasil Belajar Survei dan Pemetaan Pada Pokok Bahasan Kegunaan Pekerjaan Ukur Tanah Melalui Pengorganisasian Materi Model Elaborasi dan Buku Teks Pada Siswa Kelas 1 SMK - Tulaka, Titof (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study was to obtain information whether the learning outcomes in the survey and mapping material on the subject of the usefulness of land measurement work through the presentation of the elaboration model were better than the presentation of the textbook and to determine the interest and enthusiasm of students in learning after following the learning process through the presentation of the elaboration model. The technique used in data collection was organizing the Elaboration Model material in the Experimental class and presenting it according to the Textbook in the control class in the study was in the learning process using the Elaboration Model teaching had a positive effect on student learning outcomes. The results through presentation according to the textbook, the average value was lower than the provision of Elaboration Model teaching, because students had difficulty in classifying lessons and needed a long time to understand the material. For that there are still students who have low scores, this is caused by several factors such as health, IQ and mental psychology of students.